The Effect of TCE Addition on the Performance of Catalytic Isomerization of n-Hexane - A.K. Mohammed, Abdul Halim; Al-Hassani, Maha; kareem, Samar (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
n-Hexane conversion enhancement was studied by adding TCE (Trichloro-ethylene) on feed stream using 0.3%Pt/HY zeolite catalyst. All experiments were achieved at atmospheric pressure and on a continuous laboratory unit with a fixed bed reactor at a temperature range 240-270◦C, LHSV 1-3h-1, H2/nC6 mole ratio 1-4.By adding 435 ppm of TCE, 49.5 mole% conversion was achieved at LHSV 1h-1, temperature of 270ºC and H2/nC6 mole ratio of 4, while the conversion was 18.3 mol% on the same catalyst without adding TCE at the same conditions. The activation energy decreased from 98.18 for pure Pt/HY zeolite to 82.83 kJ/mole by adding TCE. Beside enhancement the activity, selectivity and product distribution enhanced by providing DMB (Dimethyl butane) which have higher octane number as compared with 0.3%Pt/HY zeolite. Indeed the increase of the 2.2-DMB/2,3DMB ratio with n-hexane conversion is more pronounced with TCE than with pure Pt/HY zeolite.